Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1351/pac-con-10-09-25
|View full text |Cite
|
Sign up to set email alerts
|

2-Substituted agelasine analogs: Synthesis and biological activity, and structure and reactivity of synthetic intermediates

Abstract: 2-Substituted N-methoxy-9-methyl-9H-purin-6-amines were synthesized either from their corresponding 6-chloro-9-methyl-9H-purines or 2-chloro-N-methoxy-9-methyl-9H-purin-6-amine. Great diversity in the amino/imino tautomeric ratios was observed and calculated based on 1 H NMR. The tautomers were identified by 1D and 2D 1 H, 13 C, and 15 N NMR techniques, and showed significant variation both in 13 C and 15 N shift values. Comparison of the tautomeric ratios with Hammett F values revealed that as the field/induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The monocyclic side chain of agelasines E and F were obtained from geraniol and β-cyclocitral [ 126 ] and pulegone [ 127 ], respectively. They modified also the substitution on the purine C2 position [ 128 , 129 , 130 ]. All those analogues were evaluated for their antimicrobial, antiprotozoal, antifouling and biofilm inhibition and cytotoxicity against a panel of human cancer cell lines and it was found that the length of the terpenyl side chain is important for bioactivity and that the presence of a methyl in the purine 2-position increased the antimicrobial and antiprotozoal activity, while amino groups increase the cytotoxicity [ 40 , 130 ].…”
Section: Synthetic Approaches Towards the Natural Alkylpurines Andmentioning
confidence: 99%
“…The monocyclic side chain of agelasines E and F were obtained from geraniol and β-cyclocitral [ 126 ] and pulegone [ 127 ], respectively. They modified also the substitution on the purine C2 position [ 128 , 129 , 130 ]. All those analogues were evaluated for their antimicrobial, antiprotozoal, antifouling and biofilm inhibition and cytotoxicity against a panel of human cancer cell lines and it was found that the length of the terpenyl side chain is important for bioactivity and that the presence of a methyl in the purine 2-position increased the antimicrobial and antiprotozoal activity, while amino groups increase the cytotoxicity [ 40 , 130 ].…”
Section: Synthetic Approaches Towards the Natural Alkylpurines Andmentioning
confidence: 99%